ASIS Cognitive Profiles of Children with Learning Disabilities - Cirık, Mevlut; Sak, Ugur; Arslan, Deniz; Karaduman, Engin; Opengin, Ercan (Anales de Psicología / Annals of Psychology, 2023)
Intelligence scales are widely used for cognitive profile analyses in the diagnosis of learning disabilities. The purpose of this study was to explore the cognitive profiles of children with learning disabilities on a new test of intelligence, the Anadolu-Sak Intelligence Scale. The intelligence test was administered to 89 children diagnosed with general learning disabilities. A matched control group (N = 92) was randomly selected from the norm sample. Data analyses included latent profile analyses and comparisons of scores across groups and within-group comparisons. The findings showed that the mean general intelligence and means of the verbal and visual ability of children with learning disabilities were in the average range but closer to the lower boundary. The mean of working memory was slightly below the average range and significantly lower than the mean of the matched control group. Latent profile analyses showed three distinct profiles: the zigzag profile, wavy profile, and waterfall profile. The only weakness shared by the three profiles is visual sequential processing memory. The results imply that weak sequential processing memory may contribute to learning disabilities.